Students Perception of Civic Engagement to Improve Spatial Intelligence in SMPN Batola Regency - Sigit Triyono; Ersis Warmansyah Abbas; Mutiani Mutiani; Fatwa Nur'aini; Muhammad Rijali Rahman; Ahmad Fazri (Program Studi Pendidikan IPS, 2025)
This study aims to examine the influence of civic engagement perception on the spatial intelligence of junior high school students in Barito Kuala Regency. The background of the research departs from the importance of social involvement in supporting spatial cognitive abilities which are crucial for student development. The research method uses quantitative with Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis, involving 81 students as a sample. The results of the analysis showed a significant influence between civic engagement and spatial intelligence, with a path coefficient value of 0.833 for engagement to civic variables, as well as the contribution of intelligence to civic (0.766) and spatial to civic (0.696). In addition, it was also found that external factors in the form of socio-economic background and school facilities also play a role in optimizing the development of students' spatial intelligence. The conclusion of the study confirms that strengthening civic engagement can improve spatial intelligence, so strategic recommendations are needed to integrate social engagement activities in learning to support students' spatial cognitive development effectively and contextually.